New Attractant Lures for Sampling Conistra vaccinii L. Populations: Bisexual Lures and a Sex Attractant (Lepidoptera: Noctuidae) - Szabolcs Szanyi; Zoltán Varga; Antal Nagy; Gábor Szőcs; Júlia Katalin Jósvai; Miklós Tóth (Insects, 2025)
The chemical ecology and host plant preferences of the different Conistra species (Lepidoptera: Noctuidae, Xylenini) are mostly unknown, even though they are essential components of the herbivorous assemblages of temperate zone forests. During field studies, (Z)-7-tetradecenyl acetate (Z7-14Ac) was identified as a sex attractant of Conistra vaccinii. Phenylacetaldehyde-based synthetic and iso-amyl alcohol-based semi-synthetic lures also attracted C. vaccinii, C. rubiginea, and C. rubiginosa, and in the case of C. vaccinii, they performed better than the newly identified sex attractant. The different efficiencies of the two bisexual lures probably reflected the different feeding source preferences of the species caught. The tested lures attracted both sexes and, thus, we can estimate the actual sex ratio. These traps can be used especially in applications where female samples are needed, i.e., surveys on the reproduction biology of moths (e.g., polyandry), or in surveys of population dynamics.